DETERMINANT OF THE GROWTH OF ISLAMIC BANKING BY MODERATING VARIABLES OF SAVINGS INTEREST RATE AND CREDIT INTEREST RATE EVIDENCE FROM BANTEN, INDONESIA - Ichwanudin, Wawan; Worasutr, Asas; Kambara, Roni; Indriana, Ina (RMUTT Global Business and Economics Review, 2025)
This study aims to identify the key determinants of the growth of Islamic banking in Banten Province, Indonesia, and to examine whether the presence of conventional banks acts as a moderating factor in this growth. The research utilizes monthly data spanning the period from 2019 to 2022. The analysis methods employed include Moderating and Multiple Linear Regression, which were conducted using the SPSS program version 22. Findings from this research reveal that the savings profit-sharing and financing profit-sharing significantly impact the growth of Islamic banking. Furthermore, the growth of Islamic bank assets is found to have a significant positive effect on overall Islamic banking growth. The savings interest rate is found to moderate the relationship between the savings profit-sharing and Islamic banking growth, indicating an interplay between conventional banking practices and the development of Islamic financial institutions. However, the interest rate on loans does not function as a moderating variable in the relationship between financing profit-sharing and the growth of Islamic banking.